Model-driven engineering and software development : 7th International Conference, MODELSWARD 2019, Prague, Czech Republic, February 20-22, 2019, revised selected papers /: 7th International Conference, MODELSWARD 2019, Prague, Czech Republic, February 20-22, 2019, revised selected papers. (2020) - Unknown
No abstract available